ECONOMIC ASSESSMENT OF SOME AGRO FORESTRY SYSTEMS AND ITS POTENTIAL FOR CARBON SEQUESTRATION SERVICE IN INDONESIA - Ginoga, Kirsfianti L.; Wulan, Y. Cahya; Lugina, Mega; Djaenudin, Deden (Indonesian Journal of Forestry Research, 2004)
This paper  provides  several alternatives  agroforestry  and plantation   systems  to consider  for carbon  sequestration  purposes.   It is indicated  that multicropping  of  coffee multistrata  or fruit trees such as mango,  duku and durian with timber or food and vegetable crops  produces  more benefits financially and economically compared  to monoculture  of tree plantation  such as albizia. The  former  system is more attractive in terms  of  return  to labour  and land.  However,  the later system produce  more carbon  and low cost of  carbon,  which is more potential  from the  buyers point  of  view: So there  is a trade-off   from  supply  and  demand   side  for  choosing   the  best alternatives   system.   Implication   of  these  are as follows:  (i) amount   and  price  of  product   is becoming  a key factors in determining  whether  a system is more  feasible  for selling of  product or carbon  trade, and (ii) there is   a need to create incentives  system for land  owners/producers if carbon  trade is a priority.